Van Krevelen diagrams based on machine learning visualize feedstock-product relationships in thermal conversion processes - Wang, Shule; Wang, Yiying; Shi, Ziyi; Sun, Kang; Wen, Yuming; Niedzwiecki, Lukasz; Pan, Ruming; Xu, Yongdong; Zaini, Ilman Nuran; Jagodzińska, Katarzyna; Aragon-Briceno, Christian; Tang, Chuchu; et al. (Communications chemistry, 2023)
Feedstock properties play a crucial role in thermal conversion processes, where understanding the influence of these properties on treatment performance is essential for optimizing both feedstock selection and the overall process. In this study, a series of van Krevelen diagrams were generated to illustrate the impact of H/C and O/C ratios of feedstock on the products obtained from six commonly used thermal conversion techniques: torrefaction, hydrothermal carbonization, hydrothermal liquefaction, hydrothermal gasification, pyrolysis, and gasification. Machine learning methods were employed, utilizing data, methods, and results from corresponding studies in this field. Furthermore, the reliability of the constructed van Krevelen diagrams was analyzed to assess their dependability. The van Krevelen diagrams developed in this work systematically provide visual representations of the relationships between feedstock and products in thermal conversion processes, thereby aiding in optimizing the selection of feedstock and the choice of thermal conversion technique.